2002
DOI: 10.1161/01.cir.0000030935.89559.04
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Plasma Aldosterone Levels Despite Complete Inhibition of the Vascular Angiotensin-Converting Enzyme in Chronic Heart Failure

Abstract: Background-Plasma aldosterone levels are elevated in patients with chronic heart failure (CHF) taking angiotensinconverting enzyme (ACE) inhibitors. Elevated aldosterone levels may reflect incomplete inhibition of the vascular converting enzyme during long-term ACE inhibition. We simultaneously measured plasma aldosterone levels and the degree of inhibition of the vascular converting enzyme in patients with CHF. Methods and Results-Thirty-four subjects with CHF receiving the maximum recommended doses of ACE in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
54
0
3

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(60 citation statements)
references
References 19 publications
3
54
0
3
Order By: Relevance
“…10 the inability of angiotensin-converting enzyme (ACE) inhibition to provide for sustained suppression of plasma ALDO in patients with CHF, 11,12 which indicated that the regulation of its secretion by zona glomerulosa cells of the adrenal cortex is more complex than that governed by angiotensin II (Ang II) alone; and finally, the results of a controlled clinical trial (Randomised ALdactone Evaluation Study [RALES]), conducted in 19 countries on five continents in over 1,600 patients with CHF, wherein spironolactone (vis-à-vis placebo), in combination with an ACE inhibitor (ACE-I) and loop diuretic, reduced the risk of allcause and cardiac-related mortality and cardiovascular morbidity by 30%. 13 Herein, less well recognised properties of ALDO, mediated by receptor-ligand binding, are briefly reviewed.…”
Section: Introductionmentioning
confidence: 99%
“…10 the inability of angiotensin-converting enzyme (ACE) inhibition to provide for sustained suppression of plasma ALDO in patients with CHF, 11,12 which indicated that the regulation of its secretion by zona glomerulosa cells of the adrenal cortex is more complex than that governed by angiotensin II (Ang II) alone; and finally, the results of a controlled clinical trial (Randomised ALdactone Evaluation Study [RALES]), conducted in 19 countries on five continents in over 1,600 patients with CHF, wherein spironolactone (vis-à-vis placebo), in combination with an ACE inhibitor (ACE-I) and loop diuretic, reduced the risk of allcause and cardiac-related mortality and cardiovascular morbidity by 30%. 13 Herein, less well recognised properties of ALDO, mediated by receptor-ligand binding, are briefly reviewed.…”
Section: Introductionmentioning
confidence: 99%
“…Prolonged elevation of angiotensin II and aldosterone could be an adaptive response to maintain blood pressure on the short term, but in chronic heart failure induces detrimental effects on cardiovascular structure. Moveover, despite complete vascular ACE inhibition, plasma aldosterone levels are elevated in patients with heart failure [55]. Even the combination of ACE inhibition and angiotensin II antagonism only transiently reduces aldosterone plasma levels in patients with heart failure [56] suggesting angiotensin II-independent aldosterone production.…”
Section: Mr Antagonism In Patients With LV Dysfunction and Heart Failurementioning
confidence: 99%
“…Aldosterone and eplerenone retain potassium and have direct effects on the myocardium. Because aldosterone levels are often increased despite RAAS blockade,7 simultaneous application of MRA has an additive effect over ACE inhibitors and angiotensin receptor blockers.…”
mentioning
confidence: 99%